Cardiovascular biomarkers in clinical studies of type 2 diabetes. Issue 6 (5th March 2018) - Baldassarre, Maria P. A.; Andersen, Andreas; Consoli, Agostino; Knop, Filip K.; Vilsbøll, Tina
Abstract : When planning cardiovascular (CV) studies in type 2 diabetes (T2D), selection of CV biomarkers is a complex issue. Because the pathophysiology of CV disease (CVD) in T2D is multifactorial, ideally, the selected CV biomarkers should cover all aspects of the known pathophysiology of the disease. This will allow the researcher to distinguish between effects on different aspects of the pathophysiology. To this end, we discuss a host of biomarkers grouped according to their role in the pathogenesis of CVD, namely: (1) cardiac damage biomarkers; (2) inflammatory biomarkers; and (3) novel biomarkers (oxidative stress and endothelial dysfunction biomarkers). Within each category we present the best currently validated biomarkers, with special focus on the population of interest (people with T2D). For each individual biomarker, we discuss the physiological role, validation in the general population and in people with T2D, analytical methodology, modifying factors, effects of glucose‐lowering drugs, and interpretation. This approach will provide clinical researchers with the information necessary for planning, conducting and interpreting results from clinical trials. Furthermore, a systematic approach to selection of CV biomarkers in T2D research will improve the quality of future research.